Evaluación de erosión hídrica en suelos bajo cobertura forestal y agrícola, en la Cuenca del Río Reventazón, Costa Rica. - Gaitán-Álvarez, Johanna (Instituto Tecnológico de Costa Rica, 2013)
Reventazón River Basin is one of the most important for the agricultural production and electricity generation. However agricultural activities have caused high levels of erosion and sediment accumulated in the reservoirs of hydroelectric dams, causing economic losses and decreased the generation of electricity and useful life of reservoirs. Methodology runoff plots was used to quantify the actual rates of erosion, and compare them with theoretical data obtained with the universal soil loss equation (USLE ), which allowed to quantify the effect of vegetation on erosion. Plots were established in four different sites or treatments (A: cedar plantation and melina recently established B: cedar and cocoa plantation, C: Agricultural crop, D: grass), with 3 replicates each one. Erosion rates recorded at each site was 1.01 t ha-1 yr-1 , 1.71 t ha-1 yr-1 , 6.05 t ha-1yr-1 and 1.61 t ha -1 yr-1, respectively, which were overestimated by 73 % by USLE . An analysis of variance (ANOVA), and comparison of means Tukey (α= 0,05) on Info Stat- e was made, and it was determined that between the A, B and D sites there`s not significant differences , and that both these three differ from site C. To the conclusion that the cover will have a directly proportional effect on the loss of 3 soil, this feature to retain rainwater and assist soil against infiltration and structure thereof, significantly reducing the amount of soil removal.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2013.
Keywords: Producción agrícola; Sedimentación; Plantaciones; Embalses; Cultivos; Vegetación; Agua infiltrada